2022
DOI: 10.20338/bjmb.v16i5.346
|View full text |Cite
|
Sign up to set email alerts
|

Gait velocity and stability are correlated to muscle and bone mass loss in people with Parkinson’s disease: a preliminary study

Abstract: Background: Parkinson’s disease (PD) exacerbates muscle and bone mass loss, which is associated with several negative outcomes such as falls and disability. Thus, muscle and bone mass loss may be one mechanism for the mediator role between gait impairments and PD. Aim: To verify the relationship between the spatial-temporal gait parameters and the body composition of the lower limbs in people with PD. Method: Thirteen people with PD were evaluated on two different days: i) clinical and gait evaluation; ii) bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The demographic, sociocultural, and overall health conditions data from this dataset were compared and only found differences between the groups for gender ( p < 0.004) and BMI ( p < 0.033). Since some health and body characteristics (i.e., body composition) are related to gait deficits in people with PD (Barbieri et al, 2022 ), these factors should be considered when analyzing gait data from people with PD and neurologically healthy people. Regarding the gender differences, it has been pointed out that females and males with PD present specific phenotypes concerning the symptoms of the disease (i.e., postural instability and more severe tremors in females, and more severe rigidity and bradykinesia in males) (Georgiev et al, 2017 ; Picillo et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The demographic, sociocultural, and overall health conditions data from this dataset were compared and only found differences between the groups for gender ( p < 0.004) and BMI ( p < 0.033). Since some health and body characteristics (i.e., body composition) are related to gait deficits in people with PD (Barbieri et al, 2022 ), these factors should be considered when analyzing gait data from people with PD and neurologically healthy people. Regarding the gender differences, it has been pointed out that females and males with PD present specific phenotypes concerning the symptoms of the disease (i.e., postural instability and more severe tremors in females, and more severe rigidity and bradykinesia in males) (Georgiev et al, 2017 ; Picillo et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…One of the main clinical relevance of understanding the mechanisms and factors linked with whether and how age-and age-related diseases affect walking is centered on developing or optimizing intervention strategies (e.g., prevention and rehabilitation). Not differently, papers composing this special issue suggested 12,22 , or even directly indicated 23 , training strategies for general or specific aspects related to improving walking. Barbieri and colleagues 12 suggested that exercise programs focusing on maintaining body composition (especially with a mechanical load) would reflect in the maintenance of walking speed and stability.…”
Section: Potential Interventions and Future Directionmentioning
confidence: 99%
“…Not differently, papers composing this special issue suggested 12,22 , or even directly indicated 23 , training strategies for general or specific aspects related to improving walking. Barbieri and colleagues 12 suggested that exercise programs focusing on maintaining body composition (especially with a mechanical load) would reflect in the maintenance of walking speed and stability. Becker and Rietdyk 22 also briefly mentioned, because of the link between fatigue increasing the risk of trips, the relevance of intervention programs in improving endurance capacity.…”
Section: Potential Interventions and Future Directionmentioning
confidence: 99%